Prevalence of depressive symptoms in teachers and associated factors (Research, Society and Development, 2022)
This study aimed to evaluate the prevalence of depressive symptoms in teachers and the probable associated factors. This is a quantitative, descriptive, cross-sectional study carried out with teachers from the 1st to the 9th year of elementary school at three state schools in Montes Claros, Minas Gerais. The information was collected between July and August 2020, via Google Forms. The Patient Health Questionnaire-9 (PHQ-9), Voice Disorder Screening Index (ITDV) and a sociodemographic, occupational questionnaire on habits and comorbidities were applied. The data obtained were transferred to the Software Statistical Package for the Social Sciences - SPSS version 20.0. In the statistical analysis, Poisson regression was used. A total of 82 teachers participated in the study, 90.2% of which were female, with a mean age of 43.3 years, with a workload of more than 20 hours per week (70.7%). Depressive symptoms were observed in 48.8%, of which 31.7% had mild symptoms; 7.3%, moderate; 3.7% moderately severe; and 6.1%, severe symptoms. There was statistical significance between these symptoms and vocal disorder (CI: 1.023-1.338) and lack of vocal warm-up (CI: 1.118-1.535). It is concluded that the prevalence of depressive symptoms is high in the population studied and this emotional problem can harm the voice.